Research on the visual search behavior and decision-making ability of basketball referees - Wang, Rishu; Chen, Long; Wu, Yidong; Zhang, Qi (Frontiers in Psychology, 2025)
BackgroundIn sports, basketball referees have to face high pressure and time constraints, efficient visual search behavior and decision-making particularly important.MethodsThis study compared different levels of experience (expert group, n = 10; non-expert groups, n = 10) examined the visual search behavior and decision-making ability of basketball referees when watching 20 game video clips through eye movement technology.ResultsThe results showed that, compared with the non-expert group, the expert group had higher decision-making accuracy (p < 0.01), and the percentage of fixations time was longer in the central area (p < 0.01), the outer area (p < 0.01) and the percentage of fixations time in the invalid area (p < 0.05). However, there were no significant differences in the number of fixations (p = 0.904), fixations duration (p = 0.363) and entropy (p = 0.213) between the expert group and non-experts.ConclusionOur research indicates that there are significant differences in the visual search behaviors of basketball referees with different experiences. These data can provide valuable insights into the visual search patterns of basketball referees in real game environments and emphasize the importance of refereeing expertise for basketball referees.